Influência da argamassa de revestimento na resistência à compressão em prismas de alvenaria resistente de blocos de concreto - Araújo Neto, Gilberto Nery de (2006)
In the Metropolitan Region of Recife some buildings had been constructed where the masonry fulfills function structural been, however, composed of blocks originally confectioned for non load-bearing masonry. This constructive system is regionally known as "coffin buildings". To take handle of the correct evaluation of the conditions of a building like these, it must be considered all the factors that, somehow, has some influence at the stability or durability of it. The present work had as objective to evaluate the influence of the covering mortar in the axial compressive strength of masonry prisms composed of concrete blocks of non load-bearing masonry. The tests had been carried through with prisms of three lined up blocks, where six samples, with fifteen copies each, had been confectioned. To minimize the effect of other variable, all prisms had been confectioned under the same conditions and with identical materials. The samples are: naked blocks; blocks with base to covering; blocks with base to covering and mortar with thicknesses 1,5 cm and 3 cm and traces 1:2:9 (weak) and 1:1:6 (average). The materials had been tested to define its characteristics. All the prisms had been breached at a hydraulical press for to define its respective resistances to the axial compression and the results, later, were statistically treated. It had a considerable increment at the resistance to the compression of the covered prisms and the mortar s resistance revealed influent to the resistance of the prism and the standards of rupture in the majority of the cases